THE IMPACT OF DIGITAL MARKETING ON MARKETING OUTCOMES OF SMES THE MEDIATING ROLE OF INNOVATIVE PRODUCT DEVELOPMENT - Sundari, Eva; Afwa, Awliya; Pratama, Dani (Faculty of Economic and Business, University of Pasundan, 2025)
Over recent decades, digital innovations in product creation, communication, and marketing have gained significant attention in research and decision-making across businesses of various scales. Technological advancements have greatly influenced corporate marketing strategies, consumer purchasing behav-ior, and market structures. This study examines the impact of digital marketing on marketing performance in Small and Medium Enterprises (MSME) in Pek-anbaru, with product innovation as a mediating factor. Targeting SMEs that utilize digital marketing, a purposive sampling method selected 53 Pekanbaru SMEs that met the research criteria. Path analysis through Structural Equation Modeling-Partial Least Squares (SEM-PLS) was applied as the analytical method. Findings indicate that digital marketing significantly enhances both marketing performance and product innovation. Furthermore, product innova-tion directly improves marketing performance, underscoring its role as a medi-ator in the relationship between digital marketing and marketing performance in Pekanbaru MSME.